Nonlinear Observer-based Chaos Control for SPMSM with Both Uncertain Parameters and External Disturbances - Chuansheng Tang; Yuehong Dai; Yong Xiao; Yi Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper proposed a robust chaos control scheme for surface permanent magnet synchronous motor (SPMSM) drive system considering the uncertain parameters and external disturbances. A nonlinear time delay estimator is utilized to estimate the nonlinearities, uncertain parameters and disturbances of the system on line, so it is not necessarily required the exact model of the system. Then, based on the time delay estimator, a simple feedback controller, which is only related to the system errors and control input, is simple and easy to be constructed. The control gains can be obtained easily using pole placement method. The stability of the proposed control scheme is analyzed according to Lyapunov stability theory. Law-filter is also used to improve the performance of the system. Simulation results illustrate the effectiveness of the presented control method.